Meeting the Challenge of Entrepreneurship with Social Media: The Case of Tunisian Women Entrepreneurs. Issue 1 (January 2023) - Chaker, Hajer; Zouaoui, Samia
Despite the large numbers of digital women entrepreneurs around the world, the role of social media in helping them meeting the challenge of entrepreneurship is still unclear. Through semi-structured interviews, we explored the role social media plays in the businesses of eight Tunisian digital women entrepreneurs. As a part of the Middle East and North Africa region, Tunisia was an interesting context of study characterised by an interesting presence of women in all fields, especially in entrepreneurship. And yet the number of studies carried out in this context on this effect remains limited despite the high adoption rates of social media platforms. Going from the theoretical approach to data analysis, the findings show that social media helped women entrepreneurs meeting the challenge of entrepreneurship and impacted their professional lives positively.